1896 R.I. Gen. Laws 1010, tit. 30, ch. 283, § 25 - (:unkn) unknown (General Publisher, 1893)
Whenever any person shall be arrested charged with any crime or misdemeanor, or for being drunk or disorderly, or for any breach of the peace, and shall have concealed upon his person any of the weapons mentioned in section twenty-three, such person, upon complaint and conviction, in addition to the penalties provided in section twenty-four, shall be subject to a fine of not less than five dollars nor more than twenty-five dollars, and the confiscation of the weapon so found.
--
Keywords: CARRY - CONCEALED